The Effect of Mungbeans and Skim Milk Concentration on The Nutritional and Sensory Properties of Corn Milk - Sustriawan, Budi; Aini, Nur; Prihananto, V; Hardika, Yanuar (Indonesian Journal of Food Technology, 2024)
The research aims to determine the effect of adding mungbean and skim milk on the physical, chemical and sensory properties of corn milk as well as the best formula to produce the best corn milk. The experimental design used was a factorial randomized block design. The factors studied were the addition of green beans consisting of three levels, namely 10, 20 and 30% and the concentration of skim milk consisting of three levels, namely 3, 9 and 15%. Three repetitions were carried out to obtain 27 experimental units. The results showed that the higher the addition of green beans, the lower the viscosity and protein content. The higher the concentration of skim milk used, the higher the total dissolved solids, the lower the water content, and the higher the fat content. Determining the best treatment using the Multiple Attribute Method. Sweet corn milk with the addition of 10% green beans and 3% skim milk was the best treatment with total dissolved solids of 11.67oBrix; viscosity 27.9 cP; moisture 86.1%; ash content 0.357%; fat content 0.643%; protein content 1.69; whitish yellow color (3.35); slightly strong corn aroma (3.28); slightly thick (3.23); delicious flavor (3.67); and favorable (3.63).